Moral Values in the Character of Ale in Brian Krisna’s Novel A Bowl of Chicken Noodles Before Death - Fitri Wulansari; Adinda Permata; Agil Purwitasari; Didimus Yanto; Salsa Billa; Shela Dwi Ananda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to describe the ethical values embodied in the character of Ale in Brian Khrisna’s work titled A Bowl of Chicken Noodles Before Death by applying a qualitative descriptive method based on a literature review. Research data were drawn from narrative excerpts, dialogues, and the main character’s behavior, analyzed using content analysis techniques. The findings reveal various moral values, such as gratitude, compassion, empathy, honesty, patience, a never-give-up spirit, the ability to forgive, and self-acceptance, which reflect positive human interactions with God, one another, and oneself. Ale’s character development shows a shift from a state of depression and despair toward a more positive understanding of life through the experiences and social interactions he undergoes. This novel serves not only as a form of entertainment but also as a tool for moral education that can shape the reader’s character and provide insight into the meaning of life.